Characterization and Identification of Differentially Expressed Genes Involved in Thermal Adaptation of the Hong Kong Oyster Crassostrea hongkongensis by Digital Gene Expression Profiling - Li, Jun; Zhang, Yuehuan; Mao, Fan; Tong, Ying; Liu, Ying; Zhang, Yang; Yu, Ziniu (Frontiers in Marine Science, 2017)
Thermal exposure of sessile marine animals inhabiting estuarine intertidal regions is a serious concern with respect to their physiological processes. Organisms living in this region can be exposed to high temperature (>40 °C) during the low tide, which may affect the survival of these organisms. The Hong Kong oyster, Crassostrea hongkongensis, distributed along the coast waters of the South China Sea, is one of the dominant sessile inhabitants of marine intertidal region which undergoes large seasonal temperature fluctuations (up to 10-20 °C during diurnal cycles) every year. To cope with acute thermal stress, it has developed several adaptation mechanisms, eg the firmly shut of the shells. However, the genetic basis of these mechanisms remain largely unclear. To better understand how acute thermal exposure affects the biology of the oyster, two cDNA libraries obtained from the gill of oysters exposed to 37 °C thermal stress and ambient temperature were sequenced using the Digital Gene Expression (DGE) tag profiling strategy. In total, 5.9 and 6.2 million reads were obtained from thermal stress and control libraries respectively, with approximately 74.25% and 75.02% of the reads mapping to the C. hongkongensis reference sequence. A total of 605 differentially expressed transcripts could be detected in the thermal stress group as compared to the control group, of which 378 are up-regulated and 227 are down-regulated. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that these Differentially Expressed Genes (DEGs) were enriched with a broad spectrum of biological processes and pathways, including those associated with chaperones, antioxidants, immunity, apoptosis and cytoskeletal reorganization. Among these significantly enriched pathways, protein processing in the endoplasmic reticulum was the most affected metabolic pathway, which plays an important role in the unfolded protein response (UPR) and ER-associated degradation (ERAD) processes. Our results demonstrate the complex multi-modal cellular response to thermal stress in C. hongkongensis.